2012
DOI: 10.1088/0952-4746/32/4/373
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of factors for estimating the scatter of diagnostic x-rays from walls and ceiling slabs

Abstract: Computed tomography (CT) scanning rooms and interventional x-ray facilities with heavy workloads may require the installation of shielding to protect against radiation scattered from walls or ceiling slabs. This is particularly important for the protection of those operating x-ray equipment from within control cubicles who may be exposed to radiation scattered from the ceiling over the top of the protective barrier and round the side if a cubicle door is not included. Data available on the magnitude of this te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Fog and Cormack (2010) concluded that, "For CT emissions, scatter over the shielding barrier can be considerable." Martin et al (2012) similarly state that, "The level of radiation scattered downwards from a ceiling slab into the control cubicle or into the adjacent room, is likely to exceed the protection dose criterion for virtually all CT scanning facilities." Calculations using the present model further support the premise that contributions to personal dose for individuals adjacent to CT scanner suites cannot be regarded as negligible or inconsequential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fog and Cormack (2010) concluded that, "For CT emissions, scatter over the shielding barrier can be considerable." Martin et al (2012) similarly state that, "The level of radiation scattered downwards from a ceiling slab into the control cubicle or into the adjacent room, is likely to exceed the protection dose criterion for virtually all CT scanning facilities." Calculations using the present model further support the premise that contributions to personal dose for individuals adjacent to CT scanner suites cannot be regarded as negligible or inconsequential.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in beam quality will invariably affect the scatter ratios. Moreover, Martin et al (2012) simplified the overall equation for calculating ceiling scatter by importing coefficients that were only variable with kV, ceiling height, and barrier height, while other room geometry parameters remained fixed. Although it is acknowledged that these applied constants were based on considered estimations of typical CT room configurations, the model inherently dropped a degree of accuracy and adaptability to widely varying facility designs, particularly with respect to source and exposure locations relative to the barrier.…”
Section: Introductionmentioning
confidence: 99%
“…I have witnessed the work of such "experts", who have demonstrated little or no understanding of e.g., modern diagnostic imaging technology, or of modern healthcare delivery. Experts who deny the very real, and published phenomenon of "tertiary scatter" [10][11][12][13], using outdated paradigms for shielding design, resulting in unnecessary doses to staff and the public potentially in excess of legal limits. This is a real and serious issue, from Work Health and Safety, public health, regulatory and possible litigation perspectives.…”
Section: Professional Threatsmentioning
confidence: 99%
“…One paper that compared shielding design using NCRP 49 and NCRP 147 showed that NCRP 49 methodology overestimated the required thickness of Pb by up to 50% 10. NCRP 147 is not without criticism, however, including concerns about tertiary radiation scattered from the ceilings of CT and angiography rooms into control areas 11. For high workload rooms the dose to staff in adjacent rooms can exceed several mSv/yr 11.…”
mentioning
confidence: 99%
“…NCRP 147 is not without criticism, however, including concerns about tertiary radiation scattered from the ceilings of CT and angiography rooms into control areas 11. For high workload rooms the dose to staff in adjacent rooms can exceed several mSv/yr 11. The British Institute of Radiology's (BIR) Radiation Shielding for Diagnostic x-rays published in 200012 and updated in 2012 6 uses a different approach to shielding calculation compared to the NCRP.…”
mentioning
confidence: 99%